Neurological Effect and Clinical Manifestations of COVID-19 in Elderly Population - Ranita Rusydina Daroh; Dede Renovaldi (Muhammadiyah Journal of Geriatric, 2020)
Background: Currently there is a new world health crisis which is urgent due to the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus. The elderly can be presented as a group of patients at high risk for developing covid-19 with progressive and rapid clinical deterioration including neurological manifestations. Many reports have emerged showing that SARS-CoV-2 infection has an impact on neurological function, and even causes serious neurological damage. Purposes: to investigate the possible correlation between aging process to the severity of neurological deterioration experienced in COVID-19 infection specifically by elderly people. Methods: literature searching was conducted through PubMed, MedLine and Embase. Results: Regardless of age, the infection of SARS-CoV-2 to both central and peripheral nervous system could lead into a range of neurological deteriorations, in which also ranging in forms and severity. Conclusion: In elderly patients, despite of comorbidities, the natural degeneration process is likely being a risk factor of more severe neurological symptoms of Covid-19 infection.